Sistem Monitoring Keamanan Pada Data Center Berbasis Security Information And Event Management (Siem) Dengan Wazuh dan IDS - Iik Muhamad Malik Matin; Fadhilrahman; Asep Kurniawan; Ayu Rosyida Zain; Maria Agustin (Journal of Innovative and Creativity, 2025)
A data center is a center for managing, storing and processing important data which includes sensitive information, business applications and technology infrastructure. Due to the importance of data centers in supporting organizational operations, their vulnerability to information security threats such as cyber attacks, unauthorized access has a serious impact on daily operations. The implementation of IDS is currently not optimal because in-depth analysis is difficult and requires experts to observe it. For this reason, an effective security monitoring system is needed on an Intrusion Detection System (IDS) based on Security Information and Event Management (SIEM) using the Wazuh platform. IDS plays an important role in detecting network security threats, while SIEM provides the ability to integrate and analyze security data from various sources. This research designs and implements Wazuh integration with SIEM to strengthen detection and response capabilities against security threats. Experimental methodology is used to evaluate the performance of the developed system, with a focus on intrusion detection, log analysis and security event management. The research results show that the integration of Wazuh with SIEM provides significant improvements in monitoring capabilities and response to security threats, which will be a valuable contribution in ensuring the security of networks and sensitive data.